Musician as culture hero: exploring male-female relations in PaChihera and Simon Chimbetu’s selected songs - Tembo, Charles; Maganga, Allan T.; Nenduva, Aphios (UNISA Press, 2016)
This paper is a comparative exposition of positive male-female relations in lyrical compositions of selected Zimbabwean singers. Particular attention is on one female voice, Pah Chihera and a male voice, Simon Chimbetu. The argument avowed in this paper is that the selected musicians are sober in their appreciation of gender relations in African ontological existence. It further argues that, unlike feminists who view male-female relations as antagonistic, the two musicians celebrate cordial and mutual cohesion which is part of Shona or African heritage. Against that background, the musicians are regarded as 'culture heroes' who connect Shona and other peoples of Africa with their rich and life-furthering heritage. We therefore advance the view that the selected artists ’ social vision reflects women who are family-centred and in concert with males in struggle which is provide a platform for promoting solidarity rather than schism. Critical appreciation of the music renditions of the selected musicians is guided and oriented the Africana womanist paradigm.